The Place of Grammar in School and the Effect It Has on Students’ Mastery of Grammar - Ika Sulistyarini (LPPM Universitas Qamarul Huda Badaruddin, 2018)
This research attempted to know how grammar was taught in senior high school and to know how the students’ mastery level about grammar that had been taught. This research was conducted in SMAN 2 Salatiga. The subjects of the research were the students of SMAN 2 Salatiga especially class X1. The research data were collected from the data intextbook used by the students, teacher interviews, and students’ test. The data were analyzed descriptively and quantitatively using a series of paired-samples t-Test. The analysis of the data showed that grammar taught in the school was good enough but the application was not appropriate for the students, so the students’ mastery of grammar were very low. The results of the research were expected to offer some insight into the practice of teaching grammar in senior high school and whether it had, adequately, been able todevelop the students’ ability to use English grammar. Equipped with the insight, English teachers at senior high school could determine the best way to deal with grammar to help their students master English well.